answersLogoWhite

0

This will simplify to 27 - 12x, assuming the original equation was 7-34-2x-10x.

* * * * *

No, it will not! If the assumption is correct, it will simplify to -27-12x.

User Avatar

Wiki User

10y ago

Still curious? Ask our experts.

Chat with our AI personalities

RossRoss
Every question is just a happy little opportunity.
Chat with Ross
JudyJudy
Simplicity is my specialty.
Chat with Judy
CoachCoach
Success isn't just about winning—it's about vision, patience, and playing the long game.
Chat with Coach

Add your answer:

Earn +20 pts
Q: Simplify 7-3 4-2x -10x
Write your answer...
Submit
Still have questions?
magnify glass
imp
Continue Learning about Math & Arithmetic

What is 27 over 73 reduced to its lowest terms?

27/73 is in its simplest form.


How do you do simplest form but in mixed numbers?

Simplify the fractional part, and then rewrite it with the integer part in front. For example, if asked to simplify 715/25, all you need to do is to simplify 15/25 = 3/5. The answer, then, is 73/5.


What 73 percent as a fraction in its lowest terms?

To express 73 percent as a fraction in its lowest terms, we first convert 73 percent to a fraction by dividing it by 100. This gives us 73/100. To reduce this fraction to its lowest terms, we find the greatest common divisor (GCD) of 73 and 100, which is 1. Therefore, 73/100 is already in its lowest terms.


What is the ordered pair for 9x-2y equals 73 5x-9y equals 9?

9x - 2y = 73 . . . . . (a) 5x - 9y = 9 . . . . . (b) (a)*9: 81x - 18y = 657 (b)*2: 10x - 18y = 18 Subtract: 71x = 639 so x = 9 Substitute in (a): 81 - 2y = 73 2y = 8 so y = 4 The ordered pair is (9, 4)


How do you solve 3x2 minus 18x equals 0 also solve x2 minus 10x plus 24 equals zero also solve 2x2 minus 3x equals 8?

You really should ask these questions separately, but.... 3x2 - 18x = 0 ∴ (3x)(x - 6) = 0 ∴ x ∈ {0, 6} x2 - 10x + 24 = 0 ∴ (x - 6)(x - 4) = 0 ∴ x ∈ {4, 6} 2x2 - 3x = 8 ∴ 4x2 - 6x = 16 ∴ 4x2 - 6x + (3/2)2 = 16 + (3/2)2 ∴ (2x - 3/2)2 = 16 + 9/4 ∴ 2x - 3/2 = (73/4)1/2 ∴ 2x = 3/2 ± √(73/4) ∴ 2x = (3 ± √73) / 2 ∴ x = (3 ± √73) / 4 ∴ x ∈ {(3 - √73) / 4 , (3 + √73) / 4}